RANCANG BANGUN SISTEM PENGONTROLAN INTENSITAS CAHAYA PADA AYAM BROILER DALAM MASA BROODING MENGGUNAKAN LOGIKA FUZZY - Ezra Bale; Hendrik Djahi; Don E.D.G Pollo (Universitas Nusa Cendana, 2022)
Brooding is a period after hatching of eggs which aims to provide a comfortable environment for chicks to support optimal growth. Newly hatched chicks are not yet able to regulate their body temperature optimally. For this reason, it is necessary to use lights so that the temperature of the cage remains comfortable. Controlling light intensity is generally not maximized because the light produced is only bright and dark. This study aims to design a light control system using fuzzy logic with a range of values between light and dark. In this study, a prototype was made that utilized fuzzy logic using an Arduino mega microcontroller and a dht11 sensor to detect temperature and humidity with an incandescent lamp output. The brightness of the light is regulated by a dimmer driven by a servo motor. Fans are used to lower the temperature. Research shows that the prototype can control the light intensity according to the temperature and humidity conditions in the cage. The prototype used five chicks for 14 days, where it was found that the chicks could develop well with increased body weight, growth of feathers on the wings and tail, and good appetite, and no death occurred.